PKPU AS AN INSTITUTION THAT ATTEMPTS RESTRUCTURING TO PREVENT BANKRUPTCY - Rotua Sri Damayanti; Sardjana Orba Manullang; Retno Kus Setyowati (JILPR Journal Indonesia Law and Policy Review, 2023)
This study aims to analyze PKPU in implementing debt restructuring in Decision No. 718/K/ Pdt.Sus-Pailit/2019. jo. No. 4/ Pdt.Sus.Pembatalan Perdamaian/2019/PN.Niaga.Jkt.Pst. jo. No. 23/PKPU/2011/PN.Niaga.Jkt.Pst regarding the judge's consideration in terms of Law No. 37 of 2004 concerning Bankruptcy and PKPU. The research method used is a qualitative method using data collection techniques in the form of literature studies. This research is studied based on Law No. 37 of 2004 concerning Bankruptcy by combining the theory of justice as a Grand Theory. The results of this research are in the form of Judex Jurist considerations that grant the petition of the Applicant for the cancellation of the peace agreement that has been homologated based on Decision No. 23/PKPU/2011/PN.Niaga.Jkt.Pst because the peace agreement dated November 1, 2011, which was homologated by the court, is a decision that is final and legally binding, so it cannot be changed for any reason, let alone changes made outside the court. As well as the PKPU Applicant, PT. Arpeni Pratama Ocean Line, Tbk. has admitted everything argued by the Bankruptcy Applicant, PT. Bank CIMB Niaga, Tbk. especially regarding all substantial requirements of the PKPU Applicant.